Comprehensive study of the effect of a structural parameter of hydraulic buffer on the firing stability of grenade launchers - Nguyen Van, Dung; Bien, Vo Van; Nguyen Minh, Phu; Dao Manh, Hung (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: The article’s main goal is to present a novel method for evaluating the stability of automatic weapons mounted on tripods when firing in series. Methods: The mathematical model is established based on the theory of many-body mechanics. The Lagrange II equation is used to establish the system of differential equations of motion of mechanical system. The mathematical model considers the influence of the ground elasticity and the impact of the gunner through elastic-damping connections. Dynamic simulations were performed on the AGS-17 grenade launcher. The calculated results were then compared with the experimental results to verify the proposed model. Results: The comparison results show an unexpected confidence level between the theoretical model and experimental results. The errors in muzzle velocity and firing rate are 2.52% and 6.18%, respectively. Based on the theoretical basis of the mathematical model, the influence of some structural parameters of the hydraulic buffer on the firing stability of the automatic grenade launcher was investigated. The research results provide a reliable theoretical basis to improve, design, and manufacture hydraulic buffers for grenade launchers in particular and automatic guns in general. Conclusion: The research results presented in this paper ensure high accuracy and reliability. This paper provides a reliable scientific document for the optimal design of the overall structure of the weapon system.